Relatório de estágio curricular no Juízo Central Criminal de Lisboa - Faria, Beatriz Nunes de (2019)
This report is the portrait of five months of traineeship in the Central Criminal Court of the District of Lisbon, as a result of daily monitoring the work of a collective court and all of those who collaborate with it in the exercise of the judicial function. In addition to a brief characterization of the court, the activities carried out there and the preponderant criminality, this report also constitutes a legal investigation work on the undercover actions as a means of criminal investigation for the criminal process. Starting from the dogmatic delimitation of the concept of undercover agent, agent provocateur and other related figures, such as informers and "repentant" criminals, the applicable legal regime is analyzed in order to determine the conditions of admissibility of this figure in the portuguese legal order. At the same time, it’s necessary to look at the procedural point of view, as regards the probative implications of the use of undercover agents and their harmonization with respect for the guarantees of defense imposed by the due process. In summary, this report intends to present, on the basis of the analysis of the factuality registered during the internship, a global vision on the issues that have been put in the field of undercover actions, as a hidden means of investigation and preponderant for the fight against crime, especially in the context of drug trafficking.